Effect of Dietary Supplementation of Rice Gluten Meal and Exogenous Enzyme on Nutrient Utilization and Growth Performance of Broilers - Singh, Lakhvir; Singh, Udeybir; Sethi, A.P.S.; Lamba, J. S.; Gupta, R. (Indian Journal of Animal Nutrition, 2020)
This experiment was conducted to evaluate the effects of dietary supplementation of rice gluten meal (RGM) and enzyme on nutrient utilization and growth performance of broilers. Two-hundred-and-forty-day-old broiler chicks were randomly allocated to six groups with four replicates. isonitrogenous and isocaloric starter, grower and finisher rations were formulated with different levels of RGM and were fed to the birds. Birds of T1 (control) did not receive any supplement of RGM or enzyme; diets of the birds of group T2 contained no RGM, but was supplemented with cocktail enzyme at 100g/q feed; diets of the birds in group T3 contained 10% RGM; that of group T4 contained 10% RGM with cocktail of enzyme at100g/q feed; diet of group T5 contained 15% RGM with no enzyme; whereas, the diets of group T6 contained 15% RGM along with cocktail of enzyme at 100g/q feed. Growth performance parameters like body weight gain, feed intake, feed conversion ratio (FCR), protein efficiency ratio (PER) and calorie efficiency ratio (CER) were monitored weekly. The results showed that irrespective of enzyme supplementation inclusion of RGM at 10 and 15% of the diet improved (P<0.05) body weight gain and feed intake; but FCR, PER and CER were similar among the groups. Apparent metabolizability of N was significantly (P<0.01) higher in 10 and 15% RGM fed group as compared to control, whereas, apparent metabolizability of Ca and P were similar among the groups. Thus, it was concluded that RGM can be supplemented into broiler diets up to 15% in broiler diets without any negative effect on growth performance and nutrient utilization.